Ring-tailed coatis anointing with soap: A new variation of self-medication culture? (2016)
When following a free-living ring-tailed coati Nasua nasua group behind a tourist complex on Ilha do Campeche (an island in the State of Santa Catarina, Brazil), we observed them rubbing laundry and cleaning substances onto their bodies. In order to describe this anointing behavior, spontaneous and induced anointing sessions were studied over two visits to the island. The induced events were prompted by offering bar soap in five experimental sessions. In all experimental sessions, one to three animals of both sexes performed soap-anointing behavior. It was most commonly self-directed (self-anointing), but also sometimes applied onto others (alloanointing), or sometimes performed collectively and in close proximity to other group members. The genital area was the most often rubbed location, followed by the tail. We suggest that ringtailed coatis may be deterring ectoparasites when applying soap to their integument. Ring-tailed coatis are known for anointing their fur with resin or arthropods, but this is the first description of the use of soap. Close contact with humans and easy access to soap inadvertently left outside may have been responsible for this arbitrary innovation. Because this behavior has persisted for more than 10 years and is practiced by different age groups, we suggest that this behavior is being socially transmitted across generations within the group from older to younger individuals. © 2016 by the article author(s).